Protocol of guided antipsychotic reduction to reach minimum effective dose (GARMED) in patients with remitted psychosis based on pragmatic design. Issue 2 (22nd March 2021) - Liu, Chen‐Chung; Hsieh, Ming H.; Chien, Yi‐Ling; Liu, Chih‐Min; Lin, Yi‐Ting; Hwang, Tzung‐Jeng; Hwu, Hai‐Gwo
Abstract: Aims: Patients with psychosis intend to discontinue antipsychotic treatment for various reasons. As antipsychotic discontinuation involves a high risk of relapse, maintenance treatment is recommended by mainstream opinion even when remission is attained. To optimize the risk‐to‐benefit ratio of long‐term antipsychotic treatment, we proposed an operationalized guided dose‐reduction algorithm to serve as an intermediate approach as to achieve the lowest effective antipsychotic dose and better functioning for patients with remitted psychosis. Methods: Outpatients with a history of schizophrenia‐related psychotic disorders currently under stable medications and symptoms are eligible to register in this protocol. Patients intending for dose reduction are randomized into 2:1, guided dose reduction group (GDR) versus maintenance treatment group (MTG1). Eligible patients who do not intend to reduce antipsychotics serve as naturalistic maintenance controls (MTG2). The GDR patients reduce no more than 25% of their baseline antipsychotic dose, with at least a 6‐month stabilization period before reducing another 25% of their last dose. The timing of the next dose reduction will be determined by shared decision‐making with the patient. Following a dose reduction, the patients will receive three consecutive monthly monitoring; otherwise, they receive treatment as usual. Discussion: By employing this pragmatic‐based protocol, patients are empowered to evaluate their readiness for next dose reduction attempt. We would like to test in real‐world situations if stable patients can reduce antipsychotics not at the expense of an increased risk of relapse, so as to optimize the balance between risk‐to‐benefit ratios of long‐term antipsychotic treatment.